Rationale and design for SHAREHD: a quality improvement collaborative to scale up Shared Haemodialysis Care for patients on centre based haemodialysis. Issue 1 (December 2017) - Fotheringham, James; Barnes, Tania; Dunn, Louese; Lee, Sonia; Ariss, Steven; Young, Tracey; Walters, Stephen; Laboi, Paul; Henwood, Andy; Gair, Rachel; Wilkie, Martin
Abstract Background The study objective is to assess the effectiveness and economic impact of a structured programme to support patient involvement in centre-based haemodialysis and to understand what works for whom in what circumstances and why. It implements a program of Shared Haemodialysis Care (SHC) that aims to improve experience and outcomes for those who are treated with centre-based haemodialysis, and give more patients the confidence to dialyse independently both at centres and at home. Methods/Design The 24 month mixed methods cohort evaluation of 600 prevalent centre based HD patients is nested within a 30 month quality improvement program that aims to scale up SHC at 12 dialysis centres across England. SHC describes an intervention where patients who receive centre-based haemodialysis are given the opportunity to learn, engage with and undertake tasks associated with their treatment. Following a 6-month set up period, a phased implementation programme is initiated across 12 dialysis units using a randomised stepped wedge design with 6 centres participating in each of 2 steps, each lasting 6 months. The intervention utilises quality improvement methodologies involving rapid tests of change to determine the most appropriate mechanisms for implementation in the context of a learning collaborative. Running parallel with the stepped wedge intervention is a mixed methods cohort evaluation that employs patient questionnaires and interviews, and will link with routinely collected data at the end of the study period. The primary outcome measure is the number of patients performing at least 5 dialysis-related tasks collected using 3 monthly questionnaires. Secondary outcomes measures include: the number of people choosing to perform home haemodialysis or dialyse independently in-centre by the end of the study period; end-user recommendation; home dialysis establishment delay; staff impact and confidence; hospitalisation; infection and health economics. Discussion The results from this study will provide evidence of impact of SHC, barriers to patient and centre level adoption and inform development of future interventions to support its implementation. Trial registration ISRCTN Number:93999549, (retrospectively registered 1st May 2017); NIHR Research Portfolio: 31566